Mafātiḥ al-Ghaib dalam Tafsīr al-Ṭabarī dan Tafsīr al-Mishbāh - Ummi Muhklisoh; Faiq Ainurrofiq (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2025)
Differences in interpretation are often found among mufassirs regarding a verse or sūrah of the Quran. For instance, the interpretation of sūrah Luqmān verse 34 highlights a striking difference between classical mufassirs like Ibn Jarīr al-Ṭabarī and contemporary ones like M. Quraish Shihab in interpreting the verse about the five “keys to the unseen” or Mafātiḥ al-Ghaib. This research aims to understand al-Ṭabarī and Quraish’s ideas and comprehend the differences in their interpretations of sūrah Luqmān verse 34 based on the books Tafsīr al-Ṭabarī and Tafsīr al-Mishbāh. This research uses a qualitative approach with comparative analysis. Data collection uses documentation techniques from both books. The findings show that al-Ṭabarī views the five unseen elements as absolute, while Quraish sees some as absolute and others as relative. Their differences are particularly notable in interpreting the descent of rain and what is in the womb, with al-Ṭabarī considering them absolute secrets and Quraish viewing them as relative. However, both interpret the timing of the apocalypse, what someone will do tomorrow, and where someone will die as absolute secrets. These differences may stem from methodological shifts and varying social contexts during interpretation, as well as different sources of opinion.